In silico functional and structural insight of prenylated pyrazolocurcumin derivative associated with the PGE2 inhibition through mPGES-1 blocking - Mohd Aluwi, Mohd Fadhlizil Fasihi; Salim, Fatimah; Moyeenul Huq, A.K.M.; Rullah, Kamal; Kok Wai, Lam (Trans Tech Publications Ltd, 2021)
The search of novel mPGES-1 lead inhibitors has recently become subject of interest to medicinal chemists due to the safety in comparison to existing NSAIDs such as coxibs drugs. The recent published work revealed that prenylated pyrazolocurcumin derivative as mPGES-1 has been sucessfully designed and synthesized through computational guided 3D-QSAR approach. To improve our understanding, the present paper aimed to develop in silico functional and structural insight of the compound including pharmacophore mapping, molecular electrostatic potential (MEP) simulation using Density Functional Theory (DFT) and druglikeness prediction associated with PGE2 suppression through mPGES-1 blocking. The data collected from computational modelling studies provide important insight on the molecular conformation and further shed light towards structural modification of the future novel mPGES-1 inhibitors.